ANALYSIS OF WOMAN’S DISCOURSE BASED ON CORPUS OF WARTA FEMINIS IN 2015-2019 - Nur Islamiyatul Jannah; Ade Yolanda Latjuba; Prasuri Kuswarini (UIN Alauddin Makassar, 2022)
Warta Feminis is an online news media under the Yayasan Jurnal Perempuan (YJP) which has long been involved in feminist literacy. The vision of the Warta Feminis influences the use of language which is a representation of the ideology of the media. This research aims to determine the woman’s discourse in the text of Warta Feminis news. The research uses quantitative and qualitative methods. The data source is the news of Warta Feminis in 2015-2019. Statistical data was obtained from corpus linguistics. The research shows the frequency of words in the text of Warta Feminis news. The most frequently words are perempuan, anak, kekerasan, hak, and gender. Furthermore, the words were analyzed by using discourse analysis based on the list of concordance. The discourses that have been found in the news text of the Warta Feminis are violence against women, early marriage of girls, gender-based public policies, and the fulfillment of women's rights.